The political economy under monetary union: has the euro made a difference? - Marcel Fratzscher; Livio Stracca (European Central Bank (ECB), 2008)
Economic and Monetary Union (EMU) has transformed Europe and has created an integrated pan-European economy. Much research has focused on understanding this integration process and what benefits and costs it entails. This paper identifies a political economy channel of EMU as the monetary union implies that member states had to transfer or at least curtail their policy autonomy in several areas, such as monetary policy and fiscal policy. The paper shows that EMU has helped reduce the impact of political shocks on the domestic economy of member states but magnified the transmission of political shocks within the euro area. Equally importantly, economies with a weaker track record in terms of economic and institutional quality exhibited a significantly higher sensitivity to domestic political shocks before EMU, but not thereafter. While this may entail that EMU has brought benefits to countries with a weaker economic and institutional stability by insulating them from adverse political developments at home, a potential drawback is that it may provide weaker market discipline for domestic political stability.
Keywords: F31; F33; G14; 330; EMU; Fiscal Policy; monetary policy; political economy; political news; Stock Markets; transmission; Eurozone; Wirkungsanalyse; Konjunkturzusammenhang; Geldpolitik; Finanzpolitik; Aktienmarkt; Geldpolitische Transmission; EU-Staaten; EU-Mitgliedschaft; Schweden; Dänemark; Schweiz; Großbritannien; Ukraine